Echocardiography-based markers of subclinical cardiac dysfunction in individuals with Non-Alcoholic Fatty Liver Disease and preserved ejection fraction: Interim data from a prospective study. (March 2023) - Armandi, A.; Andreis, A.; Bellettini, M.; Caviglia, G.P.; Castelnuovo, G.; Poggiolini, I.; Rosso, C.; Del Campo, N. Perez Diaz; Abdulle, A.; Gjini, K; D'Amato, D.; Ribaldone, D.G.; et al.
Abstract : Introduction: Individuals with Non-Alcoholic Fatty Liver Disease (NAFLD) have abnormal myocardial energy metabolism and reduced coronary functional capacity, even in the absence of risk factors for cardiovascular disease (CVD). Aim: We aimed to evaluate diastolic and systolic function in NAFLD individuals with preserved ejection fraction without overt CVD. Material and Method: We prospectively included 95 patients (median age 53.0 [IQR 44.5-62.5] years, male sex 44.6%) with ultrasound-diagnosed NAFLD undergoing echocardiographic evaluation, which included speckle tracking analysis with left ventricular global longitudinal strain (GLS) measurement (Philips, Andover, US). Diastolic dysfunction was defined by mitral E/E'>9 and systolic dysfunction was defined by GLS >-18. Significant liver fibrosis (SLF) was defined by Fibrosis-4 (FIB-4) score>1.3. Results: Obesity, type 2 diabetes (T2D), arterial hypertension and dyslipidemia were present in 43.3%, 21.1%, 46.2% and 57.8% of cases, while median FIB-4 was 0.97 [0.67-1.24]. SLF, diastolic and systolic dysfunction were found in 20%, 17% and 18.3% of the total. Higher FIB-4 levels were found in both diastolic and systolic dysfunction (p=0.003 and p=0.001). SLF was associated with diastolic dysfunction (OR 6.8 [95%CI 1.8-25.5], p=0.004), showing an Area Under the Curve of 0.76 (Se 76.9%, Sp 72.2%, PPV 33.3%, NPV 94.5%). In a multiple stepwise logistic regression model including T2D, obesity, arterial hypertension, dyslipidemia, male sex and SLF, both SLF and T2D were significantly and independently associated with diastolic dysfunction (aOR of SLF 6.2 [95%CI 1.5-25.1, p=0.011). In the same regression model for systolic dysfunction, only T2D showed a significant association (aOR 4.6 [95%CI 1.3-16.8], p=0.021). Conclusion: In NAFLD patients with preserved ejection fraction, SLF by FIB-4 is associated with diastolic dysfunction independently of major risk factors for CVD. Screening echocardiography may be recommended in this population. Funding: the Italian Ministry for Education, University and Research (MIUR) under the programme "Dipartimenti di Eccellenza 2018-2022" Project code D15D18000410001.